Attitudes of Saudi young women to participate in and propose volunteer work programs in light of social and cultural obstacles - Al-azam, Miesam Fawzi Motir (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the attitudes of youth in Saudi Arabia towards participating in volunteerism programs, the suggestion programs in their volunteerism and social and cultural barriers to their participation in volunteerism. The sample of the study consisted of (293) female students from Saudi universities who participants in voluntary programs and youth organizations, and the sample of the interview consisted of (20) individuals working in committees with youth in Saudi universities, The study adopted the descriptive approach to its suitability in achieving the objectives of the study. the questionnaire and interview were used to collect data. The results showed that the attitudes of youth Saudi women towards participating in volunteerism programs were high, and the proposed programs in the implementation of volunteerism among Saudi youth women were high, most notable participation in programs that solve social problems. The social and cultural barriers to youth Saudi women participation in volunteerism is high, most notably the pursuit of livelihood and the lack of time to volunteer. The results of the interview are indications that the main programs proposed in the implementation of volunteerism are social programs that deal with groups of society who are not involved in various activities within the Saudi society, especially the elderly or the unemployed. Whereas, the main obstacles to volunteer programs for young people in Saudi universities are the absence of activities and programs that attract youth concerns lack of diversity for different age groups of young participants. The study recommended was the need to encourage university youth to practice volunteerism through the allocation of a project to serve the community within the requirements of Saudi universities.
Keywords: Volunteerism; proposed programs of volunteerism; Volunteerism barriers